Specialized nutrition improves muscle function and physical activity without affecting chemotherapy efficacy in C26 tumour‐bearing mice. Issue 3 (6th May 2021) - Wijler, Liza A.; Raats, Danielle A.E.; Elias, Sjoerd G.; Dijk, Francina J.; Quirindongo, Hanil; May, Anne M.; Furber, Matthew J.W.; Dorresteijn, Bram; van Dijk, Miriam; Kranenburg, Onno
Abstract: Background: Skeletal muscle wasting and fatigue are commonly observed in cancer patients receiving chemotherapy and associated with reduced treatment outcome and quality of life. Nutritional support may mitigate these side effects, but potential interference with chemotherapy efficacy could be of concern. Here, we investigated the effects of an ω‐3 polyunsaturated fatty acid (eicosapentaenoic acid and docosahexaenoic acid), leucine‐enriched, high‐protein (100% whey), additional vitamin D, and prebiotic fibres 'specific nutritional composition' (SNC) and chemotherapy on state‐of‐the‐art tumour organoids and muscle cells and studied muscle function, physical activity, systemic inflammation, and chemotherapy efficacy in a mouse model of aggressive colorectal cancer (CRC). Methods: Tumour‐bearing mice received a diet with or without SNC. Chemotherapy treatment consisted of oxaliplatin and 5‐fluorouracil. Tumour formation was monitored by calliper measurements. Physical activity was continuously monitored by infrared imaging. Ex vivo muscle performance was determined by myography, muscle fatty acid composition by gas chromatography, and plasma cytokine levels by Luminex xMAP technology. Patient‐derived CRC organoids and C2C12 myotubes were used to determine whether SNC affects chemotherapy sensitivity in vitro . Results: Specific nutritional composition increased muscle contraction capacity of chemotherapy‐treated tumour‐bearing mice ( P < 0.05) and enriched ω‐3 fatty acid composition in muscle without affecting treatment efficacy ( P < 0.0001). Mice receiving SNC maintained physical activity after chemotherapy and showed decreased systemic inflammation. Therapeutic response of CRC organoids was unaffected by SNC nutrients, while cell viability and protein synthesis of muscle cells significantly improved. Conclusions: The results show that specialized nutritional support can be used to maintain muscle function and physical activity levels during chemotherapy without increasing tumour viability. Therefore, nutritional strategies have potential value in promoting cancer and chemotherapy tolerance.